Successful Ziprasidone Monotherapy in a Case of Delusional Parasitosis: A One-Year Followup. (16th May 2013) - De Berardis, Domenico; Serroni, Nicola; Marini, Stefano; Rapini, Gabriella; Valchera, Alessandro; Fornaro, Michele; Mazza, Monica; Iasevoli, Felice; Martinotti, Giovanni; Di Giannantonio, Massimo
Abstract : Delusional parasitosis is characterized by the false idea that own body is infested by invisible mites, insects, or other parasites. This case report describes a 24-year-old woman with delusional parasitosis who was treated with ziprasidone monotherapy (120 mg/day) with a complete remission of delusion and followed for one year without symptom recurrences. These findings, although preliminary, indicate that further investigation of ziprasidone monotherapy for the treatment of delusional parasitosis is warranted in further trials.